From the Editor - Vrček, Neven (Journal of Information and Organizational Sciences, 2008)
The Journal of Information and Organizational Sciences – JIOS – is an interdisciplinary scientific journal with a focus on the application of information sciences and advances in organizational sciences, as well as on theoretical contemplations in the fields that impact information sciences, computer sciences and organizational sciences. JIOS is published twice a year, and is managed by a team of professionals, all of whom are employed at the Faculty of Organization and Informatics, University of Zagreb. The Journal’s name and layout have already undergone several changes. As you can see, we have transformed our visual identity, and the format of the published papers has been changed as well. However, it is not only the visual identity of the Journal that we have been working on, as we have also aimed to enhance its visibility, accessibility and referencing. As a result, we are proud to say that the number of databases the Journal is cited in has grown from one to seven, and we are putting a lot of our e. orts into broadening this number in future. As you already know, the Journal’s web address has been changed to www.jios.foi.hr and it is currently being managed by the Open Journal System, in which the entire communication from submitting the paper to its reviewing and publishing is conducted on-line. In this issue of JIOS a selection of five original scientific papers and one review paper has been included covering the following topics: modern production management, fuzzy data, software and information systems development, online privacy and security, and fraud management. We hope you will find the papers interesting and challenging for your own research. Finally, we encourage you to submit your papers and also share with us your recommendations, comments or observations about papers already published. In that respect, we would very much appreciate your willingness to become a peer-reviewer for submitted papers, and thus contribute to the rising quality of JIOS.